Effect of thermal gradient on interfacial behavior of hybrid fiber reinforced polypropylene composites fabricated by injection overmolding technique. Issue 10 (18th June 2020) - Jiang, Bingyan; Fu, Liang; Zhang, Muhan; Weng, Can; Zhai, Zhanyu
Abstract: Hybrid fiber reinforced thermoplastic composites, fabricated by overmolding technique, are a novel class of lightweight components that benefit from the high mechanical performance of continuous fiber reinforced thermoplastics (CFRT) as well as geometric complexity because of short fiber reinforced thermoplastics (SFRT) composites architecture. The heterogonous interface between CFRT and SFRT in the hybrid structure was generated when SFRT was injected on CFRT surface during overmolding processing. However, the unmatched thermal properties between SFRT and CFRT may cause the poor adhesion at the interface due to the variation of temperature. In this article, how the thermal gradient affects the interfacial properties of hybrid structures is investigated through numerical and experimental methods. The results obtained from the molecular dynamics simulation demonstrate that decreasing thermal gradient can accelerate the molecular diffusion across the interface. Thus, at lower thermal gradient, the gap at interface is gradually disappeared. The results of the interfacial strength estimated by tensile lap shear test method show that the interfacial shear strength is greatly improved by decreasing thermal gradient because of higher crystallinity and bigger spherulite size of PP matrix at interface. In addition, the fracture mechanism of hybrid structure is observed to evolve with thermal gradient. Abstract :